Medication-related osteonecrosis of the jaw: A review about etiology, risk factors, pathophysiology, and treatment - Sheetal Singar; Ajay Pratap Singh Parihar; Prashanthi Reddy; Abhishek Maurya; Vishal Bamaniya (Wolters Kluwer Medknow Publications, 2020)
Medication-related osteonecrosis of the jaw (MRONJ) is a serious adverse effect of antiresorptive and antiangiogenic medication. MRONJ is considered when a patient has exposed bone in the jaw for more than 8 weeks and has a history of antiresorptive and antiangiogenic medication with a negative history of radiotherapy. Antiresorptive and antiangiogenic medication do not independently cause necrosis of bone. Various systemic and local risk factors like dentoalveolar trauma and extraction play an important role in the development of MRONJ. MRONJ can be prevented by proper dental evaluation and by performing the required treatment before commencing antiresorptive and antiangiogenic medication.